2002
DOI: 10.1007/s00428-002-0702-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular pathology of the B cell response in synovitis of rheumatoid arthritis

Abstract: The synovitis of rheumatoid arthritis (RA) was long regarded merely as an unspecific chronic inflammatory process of minor diagnostic value and therefore did not play a major role in the understanding of the pathogenesis of RA. It is only in recent years, along with the observation that T and B cells are expanded oligoclonally in synovial tissue and that B cells are able to undergo a local germinal center (GC) reaction, that the synovial tissue has come to be regarded as a site of specific immune processes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
6

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 100 publications
2
36
0
6
Order By: Relevance
“…The data presented herein document the accumulation of mutated IgG sequences with unrelated CDR3 junctions in human samples. Despite the very small sample size (1 ϫ 2 mm 2 of endoluminal material), more than one clonal group was observed in CPS; this is in agreement with the slow process of plaque formation and progression with analogy to what has been observed in many chronic autoimmune diseases (40,41). Clonal expansion, somatic hypermutation, affinity maturation, Ig class switching, and B cell receptor revision, all demonstrated in the CPS we studied, occur within tertiary lymphoid organs after B cell and T cell priming only in the presence of a specific Ag.…”
Section: Discussionsupporting
confidence: 82%
“…The data presented herein document the accumulation of mutated IgG sequences with unrelated CDR3 junctions in human samples. Despite the very small sample size (1 ϫ 2 mm 2 of endoluminal material), more than one clonal group was observed in CPS; this is in agreement with the slow process of plaque formation and progression with analogy to what has been observed in many chronic autoimmune diseases (40,41). Clonal expansion, somatic hypermutation, affinity maturation, Ig class switching, and B cell receptor revision, all demonstrated in the CPS we studied, occur within tertiary lymphoid organs after B cell and T cell priming only in the presence of a specific Ag.…”
Section: Discussionsupporting
confidence: 82%
“…These have been reported in tissues such as the gut and joints [15,16], and have also been observed within the lung parenchyma of COPD patients [4,17]. These follicles have a B-cell core with T-cells around the periphery [17].…”
mentioning
confidence: 65%
“…Recent studies have also described T-regulatory cells within the tertiary lymphoid follicles of patients with rheumatoid arthritis [15], and in mucosal biopsies of patients with inflammatory bowel disease [16]. As follicles have a B-cell core, it has been suggested that FOXP3 + T-regulatory cells can mediate B-cell activity directly [20].…”
Section: Foxp3mentioning
confidence: 99%
“…Local B cell responses are thought to contribute to RA pathogenesis (31)(32)(33), and elevated synovial levels of BLyS and APRIL have been reported in a subset of patients (6,11,34,35). In phase I trials, synovial examination in a small number of patients with RA treated with atacicept (6,35) showed that atacicept does enter the synovium and form atacicept-BLyS complexes (6,34).…”
Section: Discussionmentioning
confidence: 99%